High‐Performance Long‐Term‐Stable Dopant‐Free Perovskite Solar Cells and Additive‐Free Organic Solar Cells by Employing Newly Designed Multirole π‐Conjugated Polymers. Issue 23 (10th April 2017) - Kranthiraja, Kakaraparthi; Gunasekar, Kumarasamy; Kim, Hyunji; Cho, An‐Na; Park, Nam‐Gyu; Kim, Seonha; Kim, Bumjoon J.; Nishikubo, Ryosuke; Saeki, Akinori; Song, Myungkwan; Jin, Sung‐Ho
Abstract : Perovskite solar cells (PSCs) and organic solar cells (OSCs) are promising renewable light‐harvesting technologies with high performance, but the utilization of hazardous dopants and high boiling additives is harmful to all forms of life and the environment. Herein, new multirole π‐conjugated polymers (P1–P3) are developed via a rational design approach through theoretical hindsight, further successfully subjecting them into dopant‐free PSCs as hole‐transporting materials and additive‐free OSCs as photoactive donors, respectively. Especially, P3‐based PSCs and OSCs not only show high power conversion efficiencies of 17.28% and 8.26%, but also display an excellent ambient stability up to 30 d (for PSCs only), owing to their inherent superior optoelectronic properties in their pristine form. Overall, the rational approach promises to support the development of environmentally and economically sustainable PSCs and OSCs. Abstract : New multirole π‐conjugated polymers are developed via a rational design approach through theoretical hindsight, further successfully subjecting them into dopant‐free perovskite solar cells as hole‐transporting materials with high power conversion efficiency (PCE) of 17.28%, and additive‐free organic solar cells as photoactive donors with high PCE of 8.26%.